Multi-method (XRF, FTIR, TGA) analysis of ancient bricks from Karabalgasun : A preliminary study - Solongo, Saran; Franken, Christina; Tengis, Saran; Ulambayar, Erdenebat; Batbayr, Tumur-Ochir (Proceedings of the Mongolian Academy of Sciences, 2020)
Ancient ceramic artefacts attracted the attention of scientists as being a chronological indicator within the archaeological context; however, they can also provide information about the tech-nology and provenance. A series of brick samples from an ancient nomadic town at Karabal-gasun (Mongolia) have been analyzed using X-ray fluorescence (XRF) spectroscopy, Fourier transform infrared spectroscopy (FTIR) and thermogravimetric (TG) analysis in order to obtain information on the performance of the kilns used and on the technological skills of ancient pot-ters.